STRATEGI KOMUNIKASI DINAS KEBUDAYAAN DAN PARIWISATA KOTA PEKANBARU DALAM MENARIK MINAT PENGUNJUNG OBJEK WISATA DAKWAH OKURA (WDO) - Siswanto, Abdul Hakim; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Pekanbaru City is famous for having its religious tourism object, one of the religious tourism objects in Pekanbaru City is the tourism object of WDO (Da'wah Tourism Okura). This WDO tourism object is a horse and archery tourist attraction, which is that this sport is a sunnah sport of the Prophet Muhammad. This is one of the basic foundations and uniqueness for this WDO attraction. The reason is based on the development of WDO attractions from 2014 to 2019, it received positive responses from various groups, one of which was the Minister of Tourism of Indonesia himself gave an appreciation of these attractions so that Riau Province won an achievement in the form of third place halal tourism in Indonesia. Therefore, the Culture and Tourism Office of Pekanbaru City is intensifying in developing this WDO tourism object. The purpose of this study is to find out the communicator strategy, the strategy to determine the communicant, the message strategy and the media strategy used by the Culture and Tourism Office of the City of Pekanbaru in attracting visitors to the WDO tourist attractionThis research uses a qualitative method using the Lasswell model theory. The subjects in this study consisted of 4 informants and also of course data collection techniques using observation, interviews and documentation. The data analysis technique in this study uses interactive Miles and Huberman and also the technical validity of the data uses triangulation and an extension of participation technique.The results of this study indicate that the Department of Culture and Tourism of the City of Pekanbaru in attracting the interest of visitors to the WDO tourist attraction the communicator strategy used is through the concept of pentahelix. Which is that this concept is a synergy with 5 elements to enhance the development of tourism. Then the strategy to determine the communicant used is through organizing events so that future tourists are more interested in becoming interested in WDO attractions and the segmentation of the communicants themselves, namely local tourists and Muslim foreigners. The message strategy used is to attract visitors to this attraction prioritized through studies of preachers although other messages related to the reality of the WDO attraction will also be pinned to other tourists. and the media strategy used is that all media will be used as one of the supporting factors in optimizing this WDO attraction.